2015
DOI: 10.1088/0004-637x/798/2/111
|View full text |Cite
|
Sign up to set email alerts
|

The Galactic Center Cloud G2 and Its Gas Streamer

Abstract: We present new, deep near--infrared SINFONI @ VLT integral field spectroscopy of the gas cloud G2 in the Galactic Center, from late August 2013, April 2014 and July 2014. G2 is visible in recombination line emission. The spatially resolved kinematic data track the ongoing tidal disruption. The cloud reached minimum distance to the MBH of 1950 Schwarzschild radii. As expected for an observation near pericenter passage, roughly half of the gas in 2014 is found at the redshifted, pre--pericenter side of the orbit… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

25
250
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 98 publications
(277 citation statements)
references
References 46 publications
25
250
2
Order By: Relevance
“…These limits on accretion rates, which are always substantially lower than the total mass of G2 (with details depending on which structure of G2 is assumed), are consistent with the observed kinematics of G2 during its pericenter passage: as noted by several studies, the orbit was purely Keplerian even after the pericenter passage (Witzel et al 2014;Pfuhl et al 2015;Valencia et al 2015). This indicates that G2 did not experience a notable loss of angular momentum and energy, which indicates rather weak interactions with the hot gas around Sgr A*.…”
Section: Discussionsupporting
confidence: 86%
See 3 more Smart Citations
“…These limits on accretion rates, which are always substantially lower than the total mass of G2 (with details depending on which structure of G2 is assumed), are consistent with the observed kinematics of G2 during its pericenter passage: as noted by several studies, the orbit was purely Keplerian even after the pericenter passage (Witzel et al 2014;Pfuhl et al 2015;Valencia et al 2015). This indicates that G2 did not experience a notable loss of angular momentum and energy, which indicates rather weak interactions with the hot gas around Sgr A*.…”
Section: Discussionsupporting
confidence: 86%
“…This agrees with observations reporting that G2 is composed of a compact head and a more widespread tail (Gillessen et al 2013b;Pfuhl et al 2015). The two components are on approximately the same orbit and are connected by a faint bridge in positionvelocity diagrams, in Gillessen et al (2013a) and lasted over one year,while G2 has been stretched substantially along its orbit by tidal shearing caused by the gravitational potential of Sgr A* Article published by EDP Sciences L16, page 1 of 4 (Pfuhl et al 2015). Test particle simulations have provided a good explanation for the dynamics of G2; the results showed that hydrodynamic effects have not been significant (e.g., Pfuhl et al 2015; see also Schartmann et al 2012).…”
Section: Introductionsupporting
confidence: 93%
See 2 more Smart Citations
“…On the other hand, Pfuhl et al (2015) argued in favour of a purely gaseous cloud nature for G2 using their Brackett-γ observations. They interpreted this source as a bright knot of a larger gas streamer that includes a G2-type object called G1 in a similar orbit, but preceding it by 13 yr. G1 and G2 could be explained as the result of the partial tidal disruption of a star (Guillochon et al 2014) or as one of many gas clumps created by the collision of stellar winds from the young stars in the Galactic centre Schartmann et al 2012).…”
Section: Introductionmentioning
confidence: 99%